Analysis of forces in single‐side linear induction motor with lateral displacement for linear metro. Issue 1 (1st January 2016) - Lv, Gang; Liu, Zhiming; Sun, Shouguang
Abstract : This study investigates the influence of lateral displacement of the primary on the thrust, vertical and lateral forces in a single‐side linear induction motor for linear metro. A three‐dimensional analytical model, which is able to consider the longitudinal and transversal end effects, overhang of the primary windings and lateral displacement, is developed to obtain the air‐gap flux density distributions along longitudinal and transverse directions as well as forces. Variations of the thrust, vertical and lateral forces with the lateral displacements are comprehensive investigated when the motor is torque motoring, negative sequence braking or regenerative braking operation. The analytically predicted results are experimentally validated by measurements on reciprocal power‐fed test rig. It shows that the thrust and vertical force of single‐side linear induction motor decrease almost linearly with the increase of the lateral displacement in all regions, and lateral force is restoring which helps centralising the railcar in the regenerative braking and most parts of motoring regions.